Korelasi Pengetahuan Gizi Ibu dengan Kejadian Stunting Balita di Puskesmas Sawan 1 Bali - ERNY ERNY; RIKA INDAH; AYLY SOEKANTO (Universitas Hang Tuah, 2022)
Abstract Background: Stunting is a chronic nutritional disorder caused by many factors and has a long-term impact. Causes are very diverse and must identify to determine treatment. A mother's knowledge about nutrition is one factor that plays an essential role in preventing and overcoming stunting. Method: quantitative analysis with a cross-sectional approach to finding the correlation between mothers' knowledge about nutrition and the incidence of stunting in toddlers at the Sawan 1 Public Health Center, Buleleng Bali. Results: The statistical analysis showed that p-value of 0.007, which means a relationship between a mother's knowledge about nutrition and the incidence of stunting in children under five at the Sawan 1 Public Health Center, Buleleng Regency, Bali Province. Conclusion: Mother's knowledge about nutrition for toddlers is highly correlated with the incidence of stunting in toddlers at the Sawan 1 Public Health Center, Buleleng Bali.